FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING: PENDEKATAN METODA REGRESI LOGISTIK - INDRA ARIFIN DJASHAN; ARYA PRADIPTA (Jurnal Bisnis dan Akuntansi, 2012)
This study aimed to analyze the factors opportunities that compared to its reference to underpricing of firms that do an initial public offering (IPO) on the Jakarta Stock Exchange. Factors that are analyzed is: the use of the auditor that does not include the group Big Four auditors, the use of underwriters that are not prestigious, the use of double declining balance depreciation methods, the total percentage of shares still held by former stockholders of more than 70%, and the age of company that under 120 months. The sample companies used in this study are companies that do an IPO on the Indonesia Stock Exchange in the year 1997 till 2002. Statistical testing technique used is logistic regression. The results showed that there was no difference between groups or individual variable, have the same opportunities on the occurrence of underpricing when compared with its reference.